2003
DOI: 10.1016/s0735-1097(02)02959-5
|View full text |Cite
|
Sign up to set email alerts
|

Increased myocardial apoptosis in patients with unfavorable left ventricular remodeling and early symptomatic post-infarction heart failure

Abstract: Our data show that in patients dying >or=10 days after AMI, myocardial apoptosis is strongly associated with and may be a major determinant of unfavorable LV remodeling and early symptomatic post-infarction HF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
126
1
5

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 181 publications
(134 citation statements)
references
References 37 publications
2
126
1
5
Order By: Relevance
“…The extent of apoptosis differs from patient to patient and is associated with the level of left ventricular remodeling following myocardial infarction. Abbate et al showed that the degree of left ventricular remodeling was directly associated with the extent of apoptosis in subjects who died shorty (10 days) after STEMI [1]. Moreover, the ex vivo measured apoptotic activity in human sera is higher in patients shorty after an MI and can predict survival in patients with heart failure [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The extent of apoptosis differs from patient to patient and is associated with the level of left ventricular remodeling following myocardial infarction. Abbate et al showed that the degree of left ventricular remodeling was directly associated with the extent of apoptosis in subjects who died shorty (10 days) after STEMI [1]. Moreover, the ex vivo measured apoptotic activity in human sera is higher in patients shorty after an MI and can predict survival in patients with heart failure [12].…”
Section: Discussionmentioning
confidence: 99%
“…Apoptosis plays an important role in the early development of heart failure and left ventricular remodeling in patients following myocardial infarction [1]. The extent of lost myocardium following acute myocardial infarction varies from patient to patient and depends on the degree of activity of apoptotic processes.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the relative resistance of cardiac myocytes to caspasedependent death, it is well established that apoptosis accounts for cardiac cell death during ischemia/reoxygenation (15,16), hypertension (17), and in maladaptive hypertrophy (18), although necrosis and autophagic cell death also play a relevant role (19). Interestingly, the space left by dead myocytes is filled by granulation tissue composed of several cell types, including macrophages, endothelial cells and fibroblasts (20), and newly synthesized extracellular matrix (ECM) (21,22), which is produced mainly by cardiac fibroblasts (23).…”
mentioning
confidence: 99%
“…Clinical observations also support this relationship. [35][36][37] In the nebivolol treated group, AI was found significantly lower than MI-control group both on day 2 and day 28 of MI. In this group, in addition to total AI, regional AI rates were also significantly lower than the MI-control group.…”
Section: Discussionmentioning
confidence: 84%